Kehidupan Berbangsa, Bernegara dan Pembinaan Kesadaran Bela Negara - Ghozali, Falah Al; Maharani, Marshanda Mutiara; Prastyowati, Fanni Choirul (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This community service initiative collaborates with Tisa Academy, a Vocational Training Institution located in Surakarta City, which we refer to as our partner. The community service we provide to our partner is related to Nationalism, Statehood, and National Awareness Development. The program aims to provide guidance to our partner concerning life as a citizen of the nation, including providing materials on the rights and responsibilities of citizens, citizen awareness in national defense, and threats that can weaken national defense.  The method used involves a literal approach, which includes planning a series of steps to solve problems or achieve goals. These steps are then transformed into a structured mental procedure using cognitive skills to achieve specific objectives. Thus, this program provides education to participants about the importance of national defense. After the guidance and consultation sessions, participants understand that the embodiment of national defense can be achieved even through simple actions.